2021
DOI: 10.2147/jir.s307841
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Neuronal Cylindromatosis Expression is Essential for Electroacupuncture-Mediated Alleviation of Neuroinflammatory Injury by Regulating Microglial Polarization in Rats Subjected to Focal Cerebral Ischemia/Reperfusion

Abstract: Background: Activated microglia are polarized into the M1 or M2 phenotype. We previously reported that electroacupuncture (EA) effectively prevented nuclear factor-κB (NF-κB) nuclear translocation and improved neuronal C-X-C motif 3 chemokine ligand 1 (CX3CL1) expression, repressing microglial activation by upregulating neuronal cylindromatosis (CYLD) expression in the periischemic cortex. However, the potential mechanisms are unclear. Therefore, we explored whether EA improved CYLD protein expression to regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 68 publications
3
5
0
Order By: Relevance
“…This paper proved that siRNA‐CX3CL1 or CX3CR1 inhibitor could inhibit central glial cell inflammation. These results are similar to previous studies (Lin, Zhan, Jiang, & Ren, 2021). Still, we innovated the idea that TSPG can inhibit inflammation and depression through CX3CL1/CX3CR1, providing a new target for the anti‐depression effect of TSPG.…”
Section: Discussionsupporting
confidence: 93%
“…This paper proved that siRNA‐CX3CL1 or CX3CR1 inhibitor could inhibit central glial cell inflammation. These results are similar to previous studies (Lin, Zhan, Jiang, & Ren, 2021). Still, we innovated the idea that TSPG can inhibit inflammation and depression through CX3CL1/CX3CR1, providing a new target for the anti‐depression effect of TSPG.…”
Section: Discussionsupporting
confidence: 93%
“…In current study, we found that NLRP3 expressed in both nucleus and cytoplasm in mVRML cells. This unusual nuclear localization of NLRP3 has also been observed in some other cells 66 68 . We speculate a difference in NLRP3 localization across cell lines according to the tissue heterogeneity, which may indicate that in mVRML cells, the cytoplasmic localization of NLRP3 may promote the assembly of inflammatory bodies, whereas its nuclear localization may be beneficial to the transcription function of inflammatory bodies.…”
Section: Discussionsupporting
confidence: 76%
“…EA at GV20, LI4, and LR3 plays anti-inflammatory and neuroprotective roles by upregulating cylindromatosis (CYLD) and CX3C motif chemokine ligand 1 (CX3CL1) expression and downregulating CX3C motif chemokine receptor 1 (CX3CR1) expression, suggesting that the crosstalk between microglia and neurons is regulated. Therefore, M1-like microglial polarization is suppressed, and M2-like microglia polarization is prompted ( 93 ). Jiang et al.…”
Section: The Mechanism Of Acupuncture Treatment Regulating Immunity I...mentioning
confidence: 99%